2005
DOI: 10.1209/epl/i2005-10258-0
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of inter-time of Strombolian explosion-quakes

Abstract: We consider long-time recorded seismic signals of Stromboli volcano to determine the inter-time distribution function of the Strombolian explosion-quakes. We show that it is Poissonian. Hence, the apparently observed periodic recurrence of the explosions is actually described by the constant rate of a Poisson process. Moreover, combining a diffusive model with the experimental inter-time distribution, we can determine the size distributions of the bubbles and infer the observed slug sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…Our results lead us to conclude that the basic seismic signature of steady state activity of Stromboli is the volcanic tremor. The explosion quakes are generated when there is the formation of a large bubble in the magmatic system due to the coalescence phenomenon [e.g., Bottiglieri et al , 2005]. We note that in Chouet et al [2003], among many results obtained by inverting seismic moment tensor and a single force distribution of a point source, the authors have shown that the size of the explosion quake signals can be directly associated to the slug sizes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results lead us to conclude that the basic seismic signature of steady state activity of Stromboli is the volcanic tremor. The explosion quakes are generated when there is the formation of a large bubble in the magmatic system due to the coalescence phenomenon [e.g., Bottiglieri et al , 2005]. We note that in Chouet et al [2003], among many results obtained by inverting seismic moment tensor and a single force distribution of a point source, the authors have shown that the size of the explosion quake signals can be directly associated to the slug sizes.…”
Section: Resultsmentioning
confidence: 99%
“…During the experiment, the Strombolian activity was particularly intense. The time interval between explosions (“intertime”) was about 3 min [ Bottiglieri et al , 2005]. This implies tremor duration lasting from 30 s to 15 min.…”
Section: Data Setmentioning
confidence: 99%
“…These will remain trapped in the mud (at rest in the conduit) until their size reaches any critical dimension (for instance, by coalescence of diffusing particles; e.g. Bottiglieri et al, 2005), allowing their uprise. If this occurs at a relatively shallow depth and if the density of the bubbles is not large enough, coalescence is also limited and this also prevents the formation of larger bubbles or slugs.…”
Section: Discussionmentioning
confidence: 99%
“…It is known as "Strombolian activity". The seismic wavefield of the Stromboli volcano has been investigated, focusing the attention on the explosion quakes (Chouet et al, 1997(Chouet et al, , 1998Del Pezzo et al, 1992;Acernese et al, 2003Acernese et al, , 2004Bottiglieri et al, 2005).…”
Section: Introductionmentioning
confidence: 99%